Charles Taylor - Groot, Ger 1954-; Vanheeswijck, Guido 1955- (Klement, 2016)
Inleiding tot het gedachtegoed van de Canadese denker (1931-)
Keywords: Taylor, Charles -- 1931-; Taylor, Charles / (Charles Margrave) / 1931-; Filosofen